Meningkatkan Keterampilan Membuat Kolase Melalui Metode Pembelajaran Langsung Bagi Anak Tunagrahita Ringan - Harahap, Sartika Dewi; Iswari, Mega (Jurnal Penelitian Pendidikan Khusus, 2022)
Learning by making collages is also very fun for children, materials and tools are easily obtained, children can be creative according to their wishes. Collages also make children practice their eye and hand coordination skills and by making collages children learn to practice solving their own problems. Direct learning method is learning that is specifically designed to improve student learning about procedural learning materials, step by step. Based on this, the researcher intends to conduct research to prove whether the direct learning method can improve collage making skills for class VIII mild mentally retarded children at SLB N Padangsidimpuan.This type of research is a type of classroom action research (CAR), with the aim of knowing how to improve the ability to make collages for mentally retarded children in class VIII at SLB N Padangsidimpuan using direct learning methods. This research was conducted in collaboration with class VIII teachers. All research activities are incorporated into several processes, namely planning, observation and reflection. The study was conducted on children with mild mental retardation for class VIII SLB N Padangsidimpuan as many as three children with the initials IM, AN and AE. The study was divided into 2 cycles in which each cycle had four stages and 3 meetings in each cycle.The results achieved by the children were: IM 31%, AN 41% and ES 36%, in the first cycle the values obtained were ES 65%, AN 68%, and IM 70%. Because the results have not reached the KKM, the second cycle with the following scores: ES 83%, AN 85%, and IM 92